P224 Evaluation of inhaled corticosteroid related pneumonia mortality in patients with COPD who would not fit the criteria for inclusion in randomised controlled trials. (14th November 2013) - Singanayagam, A; Schembri, S; Akram, AR; Archibald, R; Peet, L; Fleming, G; Taylor, J; Williamson, P; Short, P; Chalmers, J
Abstract : Background: Large randomised controlled trials such as TORCH (towards a revolution in chronic obstructive pulmonary disease (COPD) health) report an increased risk of pneumonia associated with use of inhaled corticosteroids (ICS) in COPD but no corresponding increase in pneumonia-related mortality. However, these trials exclude patients who are elderly, comorbid, have co-existing lung conditions or use long-term oxygen therapy and may not be representative of 'real-world' practice. We hypothesised that ICS use in patients that are ineligible for TORCH would be associated with increased risk of pneumonia hospitalisations and mortality. Methods: We carried out an analysis of 2 independent cohorts. The EXODUS cohort included patients admitted with COPD exacerbation and considered outcomes over 1 year including pneumonia hospitalisations and pneumonia-related mortality. The Edinburgh pneumonia study included patients hospitalised with community-acquired pneumonia with the primary outcome of 30-day mortality. A secondary analysis of patients from this cohort with spirometry-confirmed COPD during clinical stability was conducted. Results: There were 977 patients included from the EXODUS cohort. 106 patients (10.8%) were hospitalised for pneumonia and 18 patients (1.8%) had pneumonia-related mortality within 12 months of initial admission. 497 patients (50.9%) would have been ineligible for the TORCH study. In a Cox proportional hazards model, adjusting for relevant confounders, patients who were ineligible for TORCH had an increased risk of pneumonia hospitalisation (HR 1.60; 95% CI 1.04–2.45) and an increased risk of pneumonia-related mortality (HR 6.1; 95% CI 1.7–22.0). Figure 1 shows a cox adjusted survival curve for pneumonia hospitalisations in patients eligible and ineligible for TORCH. There were 376 patients with COPD included from the Edinburgh pneumonia study. The 30-day mortality rate was 12.0%. 186 patients (38.0%) would have been ineligible for TORCH. After adjustment for relevant confounders, ICS use in patients classified as ineligible for TORCH was associated with increased risk of 30-day mortality (HR 1.85 95% CI 1.00–2.41). Conclusion: Patients ineligible for RCTs such as TORCH are at increased risk of ICS related pneumonia mortality and hospitalisation. Existing studies may therefore underestimate the true impact of ICS related pneumonia in the "real-world" setting.